2010
DOI: 10.1001/archgenpsychiatry.2009.194
|View full text |Cite
|
Sign up to set email alerts
|

Limited Attentional Bias for Faces in Toddlers With Autism Spectrum Disorders

Abstract: Context Toddlers with autism spectrum disorders (ASD) exhibit poor face recognition and atypical scanning patterns in response to faces. It is not clear if face-processing deficits are also expressed on an attentional level. Typical individuals require more effort to shift their attention from faces compared with other objects. This increased disengagement cost is thought to reflect deeper processing of these socially relevant stimuli. Objective To examine if attention disengagement from faces is atypical in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
2
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(89 citation statements)
references
References 68 publications
6
79
2
2
Order By: Relevance
“…As the FGT-D was designed to be a task to measure face processing abilities in low-functioning populations, these results indicate that the FGT-D may be more sensitive overall to differences in developmental disability populations than the BFRT. In ASD, these findings are consistent with the majority of findings in the related literature reporting face processing deficits in this population (e.g., Chawarska, Volkmar, & Klin, 2010;Corbett et al, 2009;Klin et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As the FGT-D was designed to be a task to measure face processing abilities in low-functioning populations, these results indicate that the FGT-D may be more sensitive overall to differences in developmental disability populations than the BFRT. In ASD, these findings are consistent with the majority of findings in the related literature reporting face processing deficits in this population (e.g., Chawarska, Volkmar, & Klin, 2010;Corbett et al, 2009;Klin et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…First, the small sample size may have led to spurious findings and increased the chance of both Type I and II errors. However, the sample sizes in the other PWS and ASD studies on face processing are relatively small and in some cases smaller than the current study (Best et al, 2010;Chawarska et al, 2010;Halit et al, 2008;Tager-Flusberg et al, 1998;Whittington & Holland, 2011). Next, the BFRT and the FGT-D do not measure face processing methods (i.e., feature vs. a configural strategy).…”
Section: Discussionmentioning
confidence: 73%
“…Rather than measure attention to social stimuli, such as faces, which has been more extensively studied in the context of autism and autistic traits (e.g., Chawarska, & Shic, 2009;Chawarska, Volkmar, & Klin, 2010;Chevallier et al, 2012;Dawson et al, 1998Dawson et al, , 2005Elsabbagh et al, 2013;Fischer et al, 2014;Fletcher-Watson et al, 2008;Kikuchi et al, 2011;New et al, 2010;Schultz, 2005;Sheth et al, 2011;van der Geest et al, 2001), our experimental task was specifically designed to measure the ability of social feedback to shape attention to the stimuli that predict such feedback. Specifically, we measured the degree to which attention is biased towards stimuli that are associated with a high probability of being followed by valent reactions.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have provided evidence for reduced attention to social stimuli (Chawarska, & Shic, 2009;Chawarska, Volkmar, & Klin, 2010;Chevallier et al, 2012;Dawson et al, 1998Dawson et al, , 2005Kikuchi et al, 2011;Schultz, 2005), cases of unimpaired attention, with intact and robust preferences for social stimuli, have also been reported (Elsabbagh et al, 2013;Fischer et al, 2014;Fletcher-Watson et al, 2008;New et al, 2010;Sheth et al, 2011;van der Geest et al, 2001). It seems not to be the case that autism can be explained simply by a broad tendency to ignore social information across situations and contexts.…”
mentioning
confidence: 99%
“…Static images are frequently served as the visual stimuli. Some reports have suggested that individuals with ASD have poor face recognition and give decreased attention to internal features of faces such as eyes, nose and mouth compared to typical controls [6], [7], [8], [9]. Some others have stated that there is similarity in fixation pattern between individuals with ASD and with typical development [10] al.…”
Section: Introductionmentioning
confidence: 99%